The Epidemiological Characteristics and Prognostic Factors of Low-Grade Brainstem Glioma: A Real-World Study of Pediatric and Adult Patients - Liu, Zhuoyi; Feng, Songshan; Li, Jing; Cao, Hui; Huang, Jun; Fan, Fan; Cheng, Li; Liu, Zhixiong; Cheng, Quan (Frontiers in Oncology, 2020)
Purpose: Our current understanding of low-grade brainstem glioma (LGBSG) is still limited. This study was aimed to conduct a large-scale population-based real-world study to understand the epidemiological characteristics of LGBSG and determine the predictive factors of cancer specific survival (CSS) and overall survival (OS) of LGBSG patients. Patients and methods: We used Surveillance Epidemiology and End Results database to conduct this study of patients with histologically confirmed LGBSG. Patient demographics, tumor characteristics, and treatment options were compared between pediatric and adult patients. Univariate and multivariate analyses were employed to determine prognostic factors of CSS and OS. Kaplan-Meier curve and decision tree were used to confirm the prognostic factors. All variables were further identified by L1-penalized (Lasso) regression and Cox proportional hazard model and then a nomogram was established to predict the 5-year and 8-year CSS and OS rate. The precision of the nomogram was evaluated by calibration plots, Harrell’s C–index and time-dependent receiver operating characteristic. The clinical use of nomogram was estimated by decision curve analysis. Results: A cohort of 372 patients with LGBSG, including 196 pediatric and 176 adult patients was analyzed. Adult and pediatric patients showed different patterns concerning tumor size, tumor extension, and adjuvant therapy and survival rate. Further multivariate analysis revealed that ventricular system involvement and gross total resection (GTR) were independently associated with increased CSS and OS, whereas WHO grade II was independently associated with shorter CSS and OS. Radiotherapy (RT) and chemotherapy (CT) were not statistically associated with CSS and OS in multivariate analysis. All the prognostic factors were confirmed by Kaplan-Meier curve and decision tree. Kaplan-Meier curve also showed that adjuvant therapy added no benefits in non-GTR group. In addition, the nomogram was developed and proved to be discriminative and clinically useful. Conclusion: This study shows that pediatric and adult patients have different tumor characteristics, treatment options and survival rate. WHO II grade, ventricular system involvement and GTR were independent prognostic factors for CSS and OS. Adjuvant therapy showed no benefit on CSS and OS in all patients and non-GTR group. The nomogram was discriminative and clinically useful.